(untitled) (Nexus International Journal of Science and Education, 2024)
The study examined the relationship between teacher leadership training and workplace performance in Quezon 1 District, Bukidnon. A non-experimental quantitative research design was employed, and data were collected from 100 secondary school teachers in the field through stratified sampling. Modified survey questionnaires were utilized to assess teacher leadership training and its significant relation, if any, with workplace performance. The findings revealed that the overall mean score for the teacher leadership training was very extensive, indicating a pervasive level of agreement among the primary respondents. On the other hand, the overall mean score for workplace performance was very extensive, with a descriptive equivalent of very extensive. Furthermore, a significant positive relationship was observed between teacher leadership training and workplace performance, suggesting the importance and effectiveness of investing in teacher leadership development programs to improve workplace performance. This relationship indicates that participating in leadership training equips educators with valuable skills, knowledge, and confidence that positively influence their performance in the workplace. The indicators of teacher leadership training include transformational and transactional leadership styles. These findings support the existing literature highlighting the importance of proper training and development opportunities for teachers, particularly leadership skills. Thus, they emphasize the necessity for educational institutions and policymakers to prioritize and allocate resources toward implementing effective training programs to enhance teacher skills and capabilities.